DIRECT DETERMINATION OF MANGANESE IN MICROGRAM AMOUNTS OF PANCREATIC TISSUE BY ELECTROTHERMAL ATOMIC-ABSORPTION SPECTROMETRY - Rorsman, P; Berggren, P (1982)
Manganese is determined by the direct insertion of freeze-dried biological samples (1-15 μg) or by injection of 2-μl samples of perifusion medium into the graphite furnace. At the most sensitive wavelength (279.5 nm), down to 0.2 pmol of manganese can be measured in the perifusion medium as well as the endogenous manganese in the endocrine and exocrine parts of the pancreas. The latter values were 0.08 ± 0.01 and 0.16 ± 0.01 mmol Mn kg-1 (dry wt.), respectively. A less sensitive wavelength (403.1 nm) is employed for measuring the larger amounts obtained after incubating the specimens in the presence of manganese(II). © 1982.